Females Are Not Proportionally Smaller Males: Relationships Between Radius Anthropometrics and Their Sex Differences. (November 2020) - Thom, Mitchell L.; Willmore, Katherine; Surugiu, Alexandra; Lalone, Emily; Burkhart, Timothy A.
Background: Distal radius fracture reduction by internal fixation is most commonly achieved using volar locking plates (VLPs). Many standard VLP designs make little point contact with radius anatomy, and most postsurgical complications following fixation are attributed to poor implant fit. Sex differences may require consideration in implant design, as females more commonly require VLP removal. Therefore, the purpose of this research was to determine whether the relationships between measures of radius shape are proportional between the sexes.Methods: Three-dimensional radius bone geometries were created from 40 male and 34 female (mean age = 72.04 years) forearm computed tomographic scans in Mimics (Materialise NV, Leuven, Belgium). Eleven measures of radius shape were collected from each scan. Principal components analysis was performed on these measures to determine which shape variables account for the greatest differences in radius shape among individuals and between the sexes.Results: Principal component scores representing isometric radius size separated the sexes. Six anthropometric measures significantly correlated with isometric radius size for all specimens, whereas 3 and 1 measures significantly correlated with isometric radius size in males and females, respectively.Conclusions: Anthropometrics of male and female radii vary by different proportions. Using anthropometrics from both sexes to create a single implant system may not result in optimal patient fit for either sex.